Perlindungan Hak Asasi Manusia Pekerja Migran pada Piala Dunia Tahun 2022 di Qatar - Prakasa, Adinda Putri (Faculty of Law, Universitas Jambi, 2023)
Amid the euphoria of Qatar being selected as the host for the 2022 World Cup, Qatar is in the spotlight of the international community because of the human rights violations that have occurred against its migrant workers. The human rights violations referred to are migrant workers receiving inadequate wages and housing, not being granted a residence permit, poor working conditions and forced labor during preparations for the World Cup. The research method used is descriptive analysis with empirical normative research. This study aims to analyze how the protection of international law and Qatar's national law, especially regarding migrant workers in addressing issues of human rights violations during the process of preparing for and organizing the World Cup. This research also analyzes the policies of FIFA and ILO in eradicating and resolving cases of human rights violations of migrant workers at the World Cup. Based on the research results, it is known that there is international and national legal protection for Qatar in guaranteeing the fulfillment of human rights, especially migrant workers. In addition, international organizations such as the International Labor Organization (ILO) and FIFA can also take responsibility for fulfilling and protecting the human rights of migrant workers.